An investigation of implicit theories and factors implicated in sex offending theory in a non-offending population - Bourke, Ashling (Trinity College (Dublin, Ireland). School of Psychology, 2012)
This thesis set out to explore a number of constructs implicated in the sex offending literature within a sample of non-offending men. This particular sample was chosen in order to investigate the 'nonnal' presentation of such constructs, the inter-relationships between the constructs, and the methodological issues associated with the assessment of such constructs. It was expected that investigating the constructs in such a way, it would provide information on the 'normal' and in some cases 'deviant' presentation of the constructs that could then be applied to sex offenders theories, and additionally highlight the methodological issues inherent in assessing such constructs.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin.